1998
DOI: 10.1038/sj.onc.1201706
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an autoregulatory tetracycline regulated system

Abstract: Tetracycline controlled gene expression systems have become powerful tools in the analysis of gene function in mammalian cell culture as well as transgenic animals and plants. The original description of a tetracyclineregulated gene expression system is based on two plasmids, one of which constitutively expresses a tetracycline-controlled transactivator protein (tTA), a fusion protein between the tetracycline repressor of E. coli and the transcriptional activation domain of the VP16 protein of herpes simplex v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
1
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 15 publications
3
28
1
1
Order By: Relevance
“…Although the number of colonies in the control cells was not significantly affected under the Tet-off conditions, the colony size was reduced, probably due to the effect of tTA-VP16 activator protein. This is consistent with an earlier report that the tTA-VP16 protein confers morphological changes to hamster glioblastoma cells (45). These results indicated that the expression of HCV NS5A protein was growth-inhibitory to NIH3T3 cells under the tetracycline-regulated expression system.…”
Section: Establishment Of Tetracycline-regulated Ns5a-expressing Stabsupporting
confidence: 82%
“…Although the number of colonies in the control cells was not significantly affected under the Tet-off conditions, the colony size was reduced, probably due to the effect of tTA-VP16 activator protein. This is consistent with an earlier report that the tTA-VP16 protein confers morphological changes to hamster glioblastoma cells (45). These results indicated that the expression of HCV NS5A protein was growth-inhibitory to NIH3T3 cells under the tetracycline-regulated expression system.…”
Section: Establishment Of Tetracycline-regulated Ns5a-expressing Stabsupporting
confidence: 82%
“…26 However, toxicity has been reported for this vector possibly resulting from the high level of tTA expression. 36 The exact mechanism responsible for the observed differences in degree of regulation among the rAAVS1, S2 and S3 vectors remains to be elucidated. The distance between the two promoters might be one factor underlying these differences.…”
Section: Discussionmentioning
confidence: 99%
“…1 Indeed this view was supported by a study which indicates that continued high level tTA expression from an autoregulatory vector is detrimental to cell functions including growth and cell cycle. 25 By contrast cells maintained in the presence of tetracycline displayed normal growth characteristics. The toxic effects of tTA are usually attributed to the potential 'squelching' effect of the VP16 component, but the tetR component could also contribute as toxic effects have been demonstrated in plants.…”
Section: Discussionmentioning
confidence: 98%